PEMBERDAYAAN PENGELOLAH BADAN USAHA MILIK DESA DI DESA BATLALE KECAMATAN AIR BUAYA KABUPATEN BURU PROVINSI MALUKU - LEDANG, NIA ALFONSA; PANGKEY, MASJE; TAMPONGANGOY, DEYSI (Sam Ratulangi University, 2021)
Empowerment of managers is an effort to emphasize the provision of strength, ability and authoritythrough training and education, counseling, socialization and assistance to managers in managing eachtype of business being managed. Village Owned Enterprise (BUMDes) is one of the governmentprograms based on empowerment and decentralization, with this program the government has thespirit to rebuild trust with the community to work together to create an economically independentvillage community. This study uses a qualitative research type where research is descriptive in nature,namely the collection of primary and secondary data is carried out by interview which is thenprocessed and obtained the results. Research results show that the problem that hinders theempowerment of BUMDes managers in Batlale Village is the provision of work programs in the formof savings and loans, business in the marine and plantation sectors. providing infrastructure andbusiness capital which in fact do not have progress and even have not been running due to the level ofability or knowledge of the managers who have not been able to develop their own programs. Thetraining provided by the government on how to manage and develop a business as well its potentialonly happened 4 years ago. apart from that, there are several obstacles, such as the lack of attention,concern and encouragement from the community and the government in assisting managers inrunning and developing business programs. The lack of these trainings means that the governmentonly provides outreach on the performance improvement of BumDes managers in Batlale Village.Keywords : Empowerment, Management, program